SAT0382 B and T Cells Count in Minor Salivary Glands of Primary SjÖgren's Syndrome: Development and Validation of a Digital Procedure. (9th June 2015) - Costa, S.; Schutz, S.; Cornec, D.; Uguen, A.; Quintin-Roué, I.; Lesourd, A.; Pers, J.-O.; Marcorelles, P.; Saraux, A.; Devauchelle-Pensec, V.
Abstract : Background: Quantification of B and T-cells infiltrate in minor salivary glands (MSG) of primary Sjögren's syndrome (pSS) patients is an on-going challenge. It might be a powerful tool to predict pSS prognosis (1). Manual counting on serial images is the most widely used method, but is very time consuming (2). Objectives: Our objectives were to develop and evaluate an automated digital method to quantitatively assess B and T-cell infiltrate in a whole gland section. Methods: 62 complete sections of MSG from well characterized pSS patients were studied. MSG histology was analysed according to the classical Chisholm's classification, the Tarpley's score, the presence of germinal centres and the focus score. B and T-cells were respectively immunostained with CD-20 and CD-3 antibodies using red and brown chromogenes. Slides were digitized and spliced into a mosaic of smaller JPEG-format images. The digital procedure was based on colour isolation of red and brown signal for each pixel. Results were obtained as a number of pixels per JPEG-format image. The digital procedure was compared to a manual cell counting method by two pathologists, on a panel of 31 JPEG-format images. For each MSG of the cohort, digital B and T-cell counts were performed for one whole gland section. Levels of agreement between manual and digital methods were evaluated using Bland-Altman plots and ICC. Results: We found a good correlation between the number of pixels and the manual cell count. Intraclass coefficients between digital and manual quantification on the 31 JPEG-format images was excellent with ICC =0.92 (95% 0.85 -0.96) for B and T-cells. We observed a significant positive correlation between B-cell proportion (B cells/ total lymphocytic infiltrate) and the focus score (Spearman coefficient 0.463, P<0.0001). Median B-cell proportion was 2.5% (0.2-13.9) vs 30.0% (15.5-45.2) in MSG with Chisholm score 1-2 (n=24) vs 3-4 (n=38), respectively; 2.2% (0.2-6.6), 27.2% (13.0-38.9) and 48.5% (29.4-56.4) in MSG with Tarpley score of 1 (n=23), 2 (n=23), and 3-4 (n=16), respectively; and 12.3% (1.9-30.6) vs 51.4% (36.6-58.9) in MSG without germinal centres (n=50) versus MSG with germinal centres (n=12), respectively (P<0.001 for all comparisons). The time needed to analyse a whole MSG section was less than 3 minutes on average using this digital count. Conclusions: This digital procedure exhibited good levels of accuracy compared to the gold standard. Software detection produced reliable, reproductive and fast results. References: Carubbi F, Alunno A, Cipriani P, Benedetto P Di, Ruscitti P, Berardicurti O, et al. Is minor salivary gland biopsy more than a diagnostic tool in primary Sjögren's syndrome? Association between clinical, histopathological, and molecular features: a retrospective study. Semin Arthritis Rheum 2014;44:314–324. Christodoulou MI, Kapsogeorgou EK, Moutsopoulos HM. Characteristics of the minor salivary gland infiltrates in Sjögren's syndrome. J Autoimmun 2010;34:400–407. Disclosure of Interest: None declared